Preliminary studies on the origin and the phylogenetic relatedness of the sacbrood virus isolated in Vietnam - Hoa, Le Thanh; Lien, Pham Viet (Academia Journal of Biology, 2015)
The 818 nucleotides sequence of a sacbrood virus (SBV) strain isolated from Vietnam was obtained by RT-PCR (reverse transcription polymerase chain reaction), cloned into a TA-vector (Invitrogen Inc.) and sequenced. This sequence was phylogenetically analyzed with the representative corresponding SBV sequences of asian and european origins. Using MEGA2.1 program (Molecular Evolution Genetics Analysis version 2.1), the phylogenetic relatedness and molecular evolutionary analyses of the SBV strains were established. Both nucleotide and amino acid phylogenetic analysis indicated that all the SBV strains of the asian origin fall into one group being completely separated from the another group of those of the european origin. The vietnamese SBV strain closely clustered with those of the mainland China and India and a SBV strain of Nepal (SB (NP1)). These SBV strains were isolated from the infected Apis cerana honeybee. All the european SBV strains performed a distinct group completely different from the asian SBV strains, except one SBV strain isolated from Nepal (SB (NP3)). These are due to the SBV strains isolated from the infected Apis mellifera honeybee. Phylogenetic analysis revealed that the vietnamese SBV strain was of geographically asian origin, having close biogeographic relatedness with those of mainland China and the neighbouring countries.